One-Step Fluorescent Probe Product-Enhanced Reverse Transcriptase Assay - Beth A. Arnold; Robert W. Hepler; Paul M. Keller (BioTechniques, 1998)
Recently developed PCR-based reverse transcriptase (RT) assays are useful in the detection of retroviruses since they are approximately a millionfold more sensitive than conventional RT assays. However, these assays are both labor- and time-intensive. The previously described product-enhanced reverse transcriptase (PERT) assay involves a two-step RT-PCR followed by detection and quantitation of PCR products by either Southern blot or enzyme-linked immunosorbent assay (ELISA). We have modified the PERT assay to be a one-step, fluorescent probe, PCR-based RT assay that can be completed from sample dilution to final quantitative assay results in approximately 5 h without loss of assay sensitivity or specificity. The assay has a dynamic range of 6 logs, and therefore, extensive sample dilution is not necessary for quantitation. This newly enhanced fluorescent PERT assay can play an important role in the highthroughput detection of retroviral infection and characterization of RT activity.